Sistema agroforestal Quesungual: una buena práctica de adaptación al cambio climático - Gamboa Morillo, Harold; Gómez, Walter; Ibrahim, Muhammad (CATIE, Turrialba (Costa Rica), 2020)
1 fotografía, 7 tablas